Defective Protein Catabolism in Atherosclerotic Vascular Inflammation - Miyazaki, Takuro; Miyazaki, Akira (Frontiers in Cardiovascular Medicine, 2017)
Vascular inflammation in atheroprone vessels propagates throughout the arterial tree in dyslipidemic patients, thereby accelerating atherosclerotic progression. To elucidate the mechanism of vascular inflammation, most previous studies have focused on inflammation-related signals that are sent in response to vasoactive stimuli. However, it is also important to understand how normal blood vessels become defective and start degenerating. Growing evidence suggests that major protein catabolism pathways, including the ubiquitin-proteasome, autophagy, and calpain systems, are disturbed in atheroprone vessels and contribute to the pathogenesis of atherosclerosis. Indeed, dysregulation of ubiquitin-proteasome pathways results in the accumulation of defective proteins in blood vessels, leading to vascular endothelial dysfunction and apoptosis in affected cells. Impaired autophagy-lysosomal degradation affects smooth muscle cell transformation and proliferation, as well as endothelial integrity and phagocytic clearance of cellular corpses. Dysregulation of the calpain system confers proatherogenic properties to endothelial cells, smooth muscle cells, and macrophages. In this review article, we will discuss the current information available on defective protein catabolism in atheroprone vessels and its potential interrelation with inflammation-related signals.